Study Comparing of Radiologic Results of Treatment of Atrophy Nonunion by Bone Grafting and Fixation with External Fixation or Plate and Screw - حلوم, غياث; المحمد, عزت; أحمد, أحمد (Latakia University Journal -Medical Sciences Series, 2021)
Objective: This study aimed to compare osteo healing noninfected atrophic nonunion at the shaft of tibia by bone grafting and fixation either with AO external fixator or plate and screw at the side of its speed and safety of healing. Methods and patients: A retrospective observational study, included patients admitted to our institute between 2015-2018 (n=21). Simple X-Ray was performed at time of admission, after operative procedure and in consecutive intervals with a period of one month between each review. Clinical assessment of patients was performed in late reviews in addition to radiological assessment. Patients were divided into two groups depending on the type of fixation. Results: Statistical differences were found between two groups regarding the time of healing, that it was [15-20] and [19-28] weeks when the fixation was using plate or external fixator respectively. When the two groups were divided depending on the location, we found that time of healing in fixation with plate was longer than it when fixation with external fixator in the middle and distal two thirds p<0.05 and was in the middle third shorter than it in the distal third in both fixation groups. Conclusion: Fixation with external fixator leads to healing in shorter period than it with plate, therefore, we recommend to continue fixation with it in cases of atrophic nonunion in the shaft of tibia.